Cryptococcal proteases exhibit the potential to activate the latent SARS-CoV-2 spike protein - Nozethu Mjokane; Saheed Sabiu; Olufemi S. Folorunso; Onele M.N. Gcilitshana; Jacobus Albertyn; Carolina H. Pohl; Olihile M. Sebolai (Elsevier, 2024)
Background: The COVID-19 pandemic has affected more than 650 million people and resulted in over 6.8 million deaths. Notably, the disease could co-manifest with microbial infections, like cryptococcosis, which also presents as a primary lung infection. Objective: In this contribution, we sought to determine if cryptococcal supernatant (which contains secreted furin-like proteases) could activate the SARS-CoV-2 spike protein. Methods: Molecular docking of the crystal structures of the SARS-CoV-2 spike protein (target) and selected cryptococcal proteases (ligands) was executed using the high ambiguity driven protein-protein docking (HADDOCK) server, with the furin protease serving as a reference ligand. The furin protease is found in human cells and typically activates the SARS-CoV-2 spike protein.Importantly, in order to provide experimental evidence for enzymatic activity, we also assessed the biochemical efficiency of cryptococcal proteases to initiate viral entry into HEK-293 T cells by SARS-CoV-2 spike pseudotyped Lentivirus. Results: We show that the selected cryptococcal proteases could interact with the spike protein, and some had a better or comparable binding affinity for the spike protein than furin protease following an in silico comparative analysis of the molecular docking parameters. Furthermore, it was noted that the biochemical efficiency of the cryptococcal supernatant to transduce HEK-293 T cells with SARS-CoV-2 pseudovirions was comparable (p > 0.05) to that of recombinant furin. Conclusions: Taken together, these data show that cryptococcal proteases could activate the SARS-CoV-2 spike protein. In practice, it may be critical to determine if patients have an underlying cryptococcal infection, as this microbe could secrete proteases that may further activate the SARS-CoV-2 viral particles, thus undermining COVID-19 intervention measures.